Comparison of renal changes with lopinavir/ritonavir plus raltegravir or tenofovir/emtricitabine in the PROGRESS study. (August 2014) - Girard, Pierre-Marie; Cotte, Laurent; Gathe, Joseph; Renjifo, Boris; Argyropoulos, Christos; Trinh, Roger; Fredrick, Linda M; Norton, Michael; Nilius, Angela
ABSTRACT : Aim: To assess renal function changes among 172 treatment-naive subjects treated with lopinavir/ritonavir (LPV/r) plus raltegravir (RAL) or LPV/r plus tenofovir/emtricitabine in the PROGRESS study, a prospective, randomized controlled trial.Patients & methods: Serum creatinine, creatinine clearance and chronic kidney disease category were compared between groups.Results: Mean change from baseline to week 96 in creatinine clearance was smaller with LPV/r plus RAL versus LPV/r plus tenofovir/emtricitabine (-1.4 vs -7.3 ml/min; p = 0.035). Chronic kidney disease category improvement was more frequent and the mean increase in serum creatinine was smaller for the LPV/r plus RAL group. Differences in estimated renal function were also detected when the analysis was performed according to baseline demographics.Conclusion: Smaller renal function declines were observed with LPV/r plus RAL. The results from this study warrant further evaluation of the renal safety profile of nucleotide reverse transcriptase inhibitor-sparing regimens.